Pengaruh model Strength-based Counseling dalam LMS Schoology untuk meningkatkan kesehatan mental dan kesejahteraan psikologis siswa - Kadek Suranata; I Ketut Dharsana; Wayan Eka Paramartha; Kadek Ari Dwiarwati; Ifdil Ifdil (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Students’ mental health is one of the central issues during the COVID-19 pandemic. Various studies have reported increasing psychological disorders experienced by students. An effort is needed to help students improve their mental health and psychological well-being. This study reports the effect of online strength-based counseling (SBC) model through LMS Schoology. The randomized control trial experiment design performed to examining the effect of intervention on this study to students well-being, resilience and Health life style. This study involved 465 students who were randomly assigned to the first experimental group assign the online SBC through LMS Schoology, the second experimental group assign to the SBC by the paper based module counseling guide, and the third is waiting list control. Manova and Anova statistic analysis used to test the hypothesis of this study. The results of this study show that online SBC through LMS Schoology is an effective intervention to help students improve healthy lifestyles and behaviors, resilience, and well-being. The findings in this study have implications for the implementation of guidance and counseling services in schools as an effort to improve students' mental health and psychological well-being.